2011
DOI: 10.1039/c0sc00297f
|View full text |Cite
|
Sign up to set email alerts
|

Borrelidin modulates the alternative splicing of VEGF in favour of anti-angiogenic isoforms

Abstract: The polyketide natural product borrelidin 1 is a potent inhibitor of angiogenesis and spontaneous metastasis. Affinity biopanning of a phage display library of colon tumor cell cDNAs identified the tandem WW domains of spliceosome-associated protein formin binding protein 21 (FBP21) as a novel molecular target of borrelidin, suggesting that borrelidin may act as a modulator of alternative splicing. In support of this idea, 1, and its more selective analog 2, bound to purified recombinant WW domains of FBP21. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The K i of borrelidin for human ThrRS is 5 nM, whereas the K i for secondary targets such as splicing factor FBP21 or CDKs, are more than 1000-fold higher, approximately of 10 μM (26,58). Moreover, borrelidin exhibits comparable potencies in the HUVEC (human umbilical vein endothelial cells) tube formation and chicken chorionic allantoic membrane models, the concentration and composition of extracellular proteins of which is vastly different (26).…”
Section: Discussionmentioning
confidence: 90%
“…The K i of borrelidin for human ThrRS is 5 nM, whereas the K i for secondary targets such as splicing factor FBP21 or CDKs, are more than 1000-fold higher, approximately of 10 μM (26,58). Moreover, borrelidin exhibits comparable potencies in the HUVEC (human umbilical vein endothelial cells) tube formation and chicken chorionic allantoic membrane models, the concentration and composition of extracellular proteins of which is vastly different (26).…”
Section: Discussionmentioning
confidence: 90%
“…Other anti-tumorigenic effects of borrelidin, including inhibition of osteosarcoma cell migration, induction of apoptosis in acute lymphoblastic leukemia and reduction of metastasis in a mouse model of melanoma may thus also be related to the extracellular functions of TARS121323. Prior to this report, it was suggested that borrelidin's angiostatic effects may be the consequence of inhibiting or activating secondary targets or through promoting anti-angiogenic isoforms of VEGF2425. In those studies, effects on the secondary targets required μM concentrations of borrelidin, known to induce cell toxicity, thus the effects may be related to effects on intracellular TARS function or through an apoptotic response.…”
Section: Discussionmentioning
confidence: 95%
“…Human ARPE19 [24], PC3 [25], A375 [26], human lung fibroblasts [27], conditionally immortalised podocytes [13], colonic adenoma cell lines AA/C1 and the in-vitro transformed adenoma cell line 10C cells [28] were maintained as described previously. Primary human RPE cells were derived from donors from the Bristol eye bank, as previously described [14].…”
Section: Methodsmentioning
confidence: 99%